2020
DOI: 10.1002/wfs2.1378
|View full text |Cite
|
Sign up to set email alerts
|

The use of transition analysis in skeletal age estimation

Abstract: The ability to produce accurate and precise age-at-death estimates from adult skeletal remains is critical for both forensic and bioarchaeological analyses. Despite many decades of investigation, anthropologists are still heavily reliant on methods that fail to adequately capture biological variation in skeletal aging and produce estimates that are insufficient for most applications. The Transition analysis (TA) by Boldsen et al. (2002) refers to a broad category of statistical approaches used to generate prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
1
27
0
3
Order By: Relevance
“…Therefore, sampling biases inherent to modern skeletal reference material may mean they do not accurately represent the “target populations” of forensic anthropologists or bioarchaeologists (Albanese, 2003; Kimmerle, 2014; Kimmerle et al, 2008; Spradley, 2014). While it is acknowledged that donated skeletal collections do not necessarily reflect the demographics of the target samples, it is typically only the age distribution of the reference sample that is discussed, particularly in regard to age mimicry and how a biased reference sample may lead to inaccurate results in regression‐based age estimation methods (Bocquet‐Appel & Masset, 1982; Boldsen et al, 2002; Getz, 2020; Konigsberg & Frankenberg, 1994).…”
Section: The Inherent Complexities Of Reference Samplesmentioning
confidence: 99%
“…Therefore, sampling biases inherent to modern skeletal reference material may mean they do not accurately represent the “target populations” of forensic anthropologists or bioarchaeologists (Albanese, 2003; Kimmerle, 2014; Kimmerle et al, 2008; Spradley, 2014). While it is acknowledged that donated skeletal collections do not necessarily reflect the demographics of the target samples, it is typically only the age distribution of the reference sample that is discussed, particularly in regard to age mimicry and how a biased reference sample may lead to inaccurate results in regression‐based age estimation methods (Bocquet‐Appel & Masset, 1982; Boldsen et al, 2002; Getz, 2020; Konigsberg & Frankenberg, 1994).…”
Section: The Inherent Complexities Of Reference Samplesmentioning
confidence: 99%
“…Although a new version of TA software was published after this research was concluded, the findings are nonetheless meaningful because there has been a long delay between the publication of the original method and its widespread adoption (Getz, 2020), and it is likely that it will be several years before the revised software will be broadly employed. Additionally, these findings offer a more general caution: socioeconomic classes, religious identities, and political affiliations can contribute to differences in burial locations and whether or not the names of the dead are recorded.…”
Section: Discussionmentioning
confidence: 94%
“…Like other methods, TA tends to be more accurate in young adulthood. Whereas the method is more accurate for older adults, this is likely a result of the wider confidence intervals in later adulthood (Getz, 2020). To be sure, however, potential causes of decreased survivorship in the parish of St. Werburgh, including population mobility, practiced faith, occupation, and political affiliation, should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…For the mathematical and statistical underpinnings of MLE, see Hastie et al (2009). MLE is a common approach in biological anthropology and can be used across the discipline including age estimation techniques (Boldsen et al, 2002; Getz, 2020; Konigsberg, 2015; Milner & Boldsen, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The numbers represent the MLE age estimate and the ±2SD within-plus-between tooth variance age estimates probability distribution (a distribution of estimated ages). mation techniques(Boldsen et al, 2002;Getz, 2020;Konigsberg, 2015;Milner & Boldsen, 2012) Kamnikar et al (2018). adjust the numerical parameters (the median ages of attainment on the logarithmic scale) based on a modern reference sample and these values are used to estimate the ageat-death across both study sites using Shackelford et al's method.…”
mentioning
confidence: 99%